Implementation of productivity improvements in gold chains through the PDCA and 5S cycles in a jewelry company in Peru - Baldeón Cervantes, Jazmin (2024)
The jewelry industry, as one of the key subsectors within the manufacturing sector, plays a vital role in economic growth, representing 17% of the country's development. However, it faces an efficiency problem in the production process, mainly caused by unplanned machine downtime. This was evident in a jewelry manufacturing company, where the most crucial productivity factor was identified, and the DMAIC method was proposed to improve the company's efficiency. In order to achieve this, an implementation proposal based on two fundamental tools has been developed: the Plan-Do-Check-Act (PDCA) Cycle and the 5S. These tools were carefully selected due to their proven effectiveness in process optimization and reducing unplanned failures. The model was validated in a company dedicated to the supply and maintenance of dry chemical powder extinguishers in Apurímac. The results are remarkable: availability increased from 76% to 93%, performance from 39% to 95%, and quality from 43% to 95%. Efficiency also improved significantly, from 13% to 84%, demonstrating the effectiveness of the proposal. The main outcome of this research is the improvement in efficiency, directly contributing to the growth of the industry and, ultimately, the economic development of the country. This research provides an effective solution to address the low efficiency problem in the jewelry industry, demonstrating that the implementation of PDCA and 5S tools can lead to significant efficiency improvements.